Quality of Care and Health Status in Ukraine - Peabody, John W.; Luck, Jeff; DeMaria, Lisa; Menon, Rekha (BioMed Central, 2015)
We conducted a national level assessment of the quality of clinical care practice in the Ukrainian healthcare system for two important causes of death and chronic disease conditions. We tested two hypotheses: a) quality of care is predicted by physician and facility characteristics and b) health status is predicted by quality of care. Younger, female physicians provide a higher quality of care—as well as those that have had recent continuing medical education (CME) in chronic disease or health behaviors. Higher quality was associated with better health outcomes.